Postgraduate Study: An Academic Journey - Oguntibeju , Oluwafemi Omoniyi (Postgraduate Study: An Academic Journey, 2023)
Postgraduate degrees could act as conversion courses, permitting a person to change the direction of his or her study and be able to follow a dream career path. Postgraduate degree enhances the ability to understand and apply an array of speculative and thoughtful situations and be able to objectively apply alternative options. The choice of a university for postgraduate degree is very critical to the success of completing the programme. Building a strong, useful, and productive network can provide the needed support for the student during the postgraduate journey. It is good to work smartly to enhance productivity while avoiding unnecessary and unrelated multitasking that could impede progress. This book provides a simple approach to deciding for postgraduate degree, challenges that the postgraduate student may face, how to handle the challenges in relating with supervisors, doing your research, and writing your thesis etc.